Status Hukum dan Upaya Hukum Tanah Hak Guna Bangunan Pasca Pembatalan Sertipikat oleh Pengadilan Tata Usaha Negara - Nadinda Rahma; Lego Karjoko; Elizabeth Ayu Puspita Adi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Right to Build Certificate (Hak Guna Bangunan/HGB), as evidence of land rights intended to provide legal certainty for right holders, may in practice be revoked through decisions of the State Administrative Court. Such revocation creates legal uncertainty regarding the legal status of the land and the position of the right holder, particularly where the certificate holder is not a party to the proceedings. This research aims to analyze the legal status of land following the revocation of an HGB certificate and to examine the legal remedies available to right holders in order to obtain legal certainty. The research employs a normative juridical approach through a literature review of statutory regulations and court decisions. The findings indicate that following the revocation of HGB Certificate Number B 222 in the name of PT Pertamina (Persero), the land reverts to state land, with Pertamina holding priority rights pursuant to Article 37 paragraph (4) of Government Regulation Number 18 of 2021. However, legal remedies through the priority rights mechanism do not provide absolute legal certainty, as the use of the term “may” reflects governmental discretion rather than a legal obligation. Consequently, legal certainty for PT Pertamina remains conditional and dependent upon administrative discretion, rather than constituting final legal certainty.